Sleepy Boy : something different yet more convenient / Aldridge Azingere Jefferin... [et al.] - Jefferin, Aldridge Azingere; Jainuidin, Jeeophetra; Getruda, Walter; Masri, Mohd. Izzan; Sali, Ardil Adhar (2013)
Introducing the world first full wireless charging system called "Witricitity". Witricitity is using the latest concept in electrical technology where it is possible to transmit electricity from a source to a receiver without any cables or wires. This concept was devised in 2004 by a group of researchers from MIT where it is possible to provide electricity to a gadget without any batteries or wires. Witricitity works based on two coiled resonant objects which resonate at the same frequency while exchanging energy efficiently. One of these objects will be the wireless charger. Witricitity can be compared with acoustic resonances where once a sufficiently loud single note is sung in a room filled with glasses, the glass having the corresponding frequency accumulates sufficient energy to break. Using the same principles of resonance Witricitity s, uses magnetically coupled resonators where one of them, the sending unit is the wireless charger. This charger tends to fill its surrounding space with non-radioactive magnetic field that oscillates at specific MHz frequencies. This field then transmits power to the receiving unit which is designed to resonate with the magnetic field. It is the strong resonant nature of the wireless charger that ensures that there is interaction only between the charger and receiving unit and no interaction with the rest of the environment. Moreover wireless chargers are not hampered in providing energy even if there are environmental objects that obstruct the line of sight between the two coils. With a wireless charger in a room, it can charge laptops and mobiles with there being no necessity of any plugging in or using batteries.